A invenção da capital eterna : discursos sensíveis sobre a modernização de Cuiabá no período pós-divisão do Estado de Mato Grosso (1977-1985) - Amedi, Nathália da Costa (2014)
In 1977, with the division of the State of Mato Grosso and the dismemberment of the southern part of its territory, Cuiabá was faced with a new challenge. The goal at that time was to get rid of “stagnation”, the “delay” and “isolation” that seemed to live Mato Grosso and Cuiabá, the capital. Seemed to be urgent, in this context, the definition of a “new capital” city-symbol of the “new Mato Grosso” in an attempt to break away with the “backcountry” style, “bucolic” and “intimate”. Cuiabá is considered the gateway to the occupation of the Amazon, had reached the moment of creation of a new city to face Campo Grande, capital of the newly created state of Mato Grosso do Sul, a city which was called as “modern”, “clean”, “industrialized”, “new” and it was presented as a counterpoint to Cuiaba: labeled “dirty”, “old”, “delayed” – a city with strong brands colonial. The discourse employed during the period was to modernize not stagnate. Given the above the present dissertation addresses the sensitive talks on the modernization of the city of Cuiabá, in the post-period division of the state in 1977, with reference to the speech of politicians, government officials, journalists, academics and representatives of local associations representing. The time frame of this research is between the years 1977 to 1985 The analysis will be guided by three specific dates: 1977 - with the announcement of the creation of the State of Mato Grosso do Sul from the dismemberment of the State of Mato Grosso, defined as capital the city of Campo Grande, through the enactment of Complementary Law No. 31, dated October 11, 1977, signed by President Ernesto Geisel; 1979 – with the final installation of the State of Mato Grosso do Sul, on January 1, 1979; and 1985 - the period of (re) democratization of Brazil with the election of Tancredo Neves in the first election of a civilian indirect post-military dictatorship.